THE ROLE OF TOURISM IN THE SUSTAINABILITY OF ANCIENT CITIES / MOSUL'S OLD CITY AS A MODEL (American Journal of Business Management, Economics and Banking, 2023)
The problems of preserving the old city of Mosul with its historical landmarks has become one of the necessities of preserving its identity and history of Mosul, which faced great challenges of events, wars and destruction and required reconstruction in order to preserve the identity, culture and history of the old city of Mosul, and ignoring the role of tourism in preserving the old city of Mosul and its monuments of archaeological, historical, religious and cultural value, as it is not only dealing with its landmarks, but must be expanded to include what surrounds it in order to Preservation, and highlighting the stages of reconstruction witnessed by the old city of Mosul and its landmarks, and the weak interest in its buildings of historical, archaeological, cultural and religious value, and the severe lack of basic services in the old city of Mosul, which in turn makes it an obstacle to the sustainability of the old city in terms of tourism, the old city of Mosul faced a conflict between destruction and reconstruction, as the preservation of the old city of Mosul with its landmarks of tourist value has become a complex challenge, especially in the face of the destruction of its infrastructure and landmarks, and the subsequent stages of reconstruction in its various dimensions, and the developmental role of tourism in the sustainability of cities is one of the effective trends, especially in historical cities with a tourist dimension, and that sustainable tourism is one of the elements of preserving historical cities for their direct adherence to their landmarks.